PENEGAKAN HUKUM TERHADAP CYBER CRIME DI BIDANG PERBANKAN SEBAGAI KEJAHATAN TRANSNASIONAL - Kuncoro, Tri (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
ABSTRACT Internet has been used in various fields of life, one of which is banking. Banking activities are performed through Internet-banking. Through the internet-banking service, customers can conduct financial transactions without having to come to the bank. In this study addressed two issues namely the forms of cyber crime in the banking and jurisdiction in the law enforcement against cyber crime in banking. This research is a normative legal research. Legal materials collected through library research. In this research, legal materials were analyzed by using the description, interpretation, argumentation, evaluation and systematization. The forms of cyber crime in banking are typo site, keylogger / keystroke recorder, sniffing, brute-force attacking, deface web, email spamming, denial of service and virus, worm, trojan. Jurisdiction in the law enforcement against cyber crime in banking jurisdiction includes legislative, executive and enforcement jurisdiction. Jurisdiction specifically stipulated in Article 2 of Act of Republic of Indonesia Number 11 of 2008 concerning Information and Electronic Transactions. Banks should have an electronic security system to protect the system. The Law enforcement against cyber crime in banking requires cooperation between countries.
Keywords: law enforcement; jurisdiction; cyber crime; banking